Nitrocobinamide, a New Cyanide Antidote That Can Be Administered by Intramuscular Injection - Chan, Adriano (J Med Chem, 2015)
Currently available cyanide antidotes must be given by intravenous injection over 5–10 min, making them illsuited for treating many people in the field, as could occur in a major fire, an industrial accident, or a terrorist attack. These scenarios call for a drug that can be given quickly, e.g., by intramuscular injection. We have shown that aquohydroxocobinamide is a potent cyanide antidote in animal models of cyanide poisoning, but it is unstable in solution and poorly absorbed after intramuscular injection. Here we show that adding sodium nitrite to cobinamide yields a stable derivative (referred to as nitrocobinamide) that rescues cyanide-poisoned mice and rabbits when given by intramuscular injection. We also show that the efficacy of nitrocobinamide is markedly enhanced by coadministering sodium thiosulfate (reducing the total injected volume), and we calculate that ∼1.4 mL each of nitrocobinamide and sodium thiosulfate should rescue a human from a lethal cyanide exposure. [Image: see text]